Pengembangan Silabus Dan Rencana Pelaksanaan Pembelajaran Dalam Meningkatkan Profesionalisme Guru - Bani Bani (IAI Darussalam, 2015)
Professionalism development learns, now mean becomes serious attention. A variety kontinu's party do professionalism step-up effort learns. That effort dilatarbelakangi by that reality: First, task and teacher role is not simply pass on science and technology informations, but moreover forms attitude, behaviour, action, conduct, heart, and participant soul is taught that they have moral and social commitment and as mankind which can withstand at globalisasasi's era now. Both of , shall we admit that professionalism a large part our teacher still haven't be equal to. Therefore, indispensable marks sense effort for everlastingly increase teacher professionalism. Teacher shall perpetually get effort to increase its learning quality, that learning activity aim can reach optimal ala. One of the ways to increase learning quality that did by teacher is by undertaking collation and Syllabus development and Learning Performing Plan (RPP). Syllabus as a set of plan and arrangement about this curriculum development, on in essentials constitutes one of precondition in determine aim and to the effect learning. More, Syllabus and Learning Performing Plan (RPP) not only aims one bounds of teaching formalization, but at a swoop fix learning quality at brazes and increase teacher professionalism